The legal culture in Poland before the foundation of the Academy of Cracow - Lis, Artur (The Opole Studies in Administration and Law, 2017)
Culture is a very complex reality of human existence, which is comprehended in its different aspects. By the object of culture they are all products of human activity, events, behaviors ordered in certain examples present in societies in the form of rules of conduct which are determined by customs, morality and legal regulations. The acceptance of Baptism by Mieszko I of Poland in 966 was the turning point in the Polish history. The country of the first Polish Piast was rooted in the culture of the international community of European states. This situation favored the influence of certain rights of the foreign Polish legal system. In the then practice of Slavic states, the legal system was based on a tribal customary law (i.e., universally recognized, time-honored form of behaving, accepted in the given social community). From the 12th and 13th centuries the knowledge of Roman law and canon law broadened in Poland. During this period, developing the legal thought was based on both types of law. Knowledge of those systems derived from various sources. This process was used for the import of legal manuscripts of Roman and canonistic study to Poland. An example of the reception of Roman law and canon law in Poland until the beginning of the 13th century is the Chronicle of Poland by Master Vincent called Kadlubek (c. 1150–1223). The document is one of the most important and most abundant sources of law in this period.